Education for Disabilities: Analysis of Ma'na cum Maghza 'Abasa: 1-11 - Ahmad Murtaza MZ; Roma Wijaya (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
This article examines the phenomenon of education for people with disabilities in Q.S. ‘Abasa: 1-11. This study uses the ma’na cum maghza theory approach which was initiated by Sahiron Syamsuddin. This discourse arises from the problem of low access to education for people with disabilities. The study of ma’na cum maghza, using a linguistic and historical-context approach, produces a significance that is not limited to morality, but there are efforts to equalize education for people with disabilities. The results of this study indicate that inclusive access to education for persons with disabilities should be further improved, in an effort to improve the quality of education for persons with disabilities